Degradation of aniline in aqueous solution by dielectric barrier discharge plasma: Mechanism and degradation pathways. (May 2019) - Sang, Wenjiao; Cui, Jiaqi; Feng, Yijie; Mei, Longjie; Zhang, Qian; Li, Dong; Zhang, Wanjun
Abstract: The degradation of aniline solution using the dielectric barrier discharge (DBD) plasma was studied in this paper. The results indicated that the initial concentration of aniline, applied voltage and initial pH value affected the removal efficiency of aniline significantly. After 12 min with DBD plasma treatment, 90.2% removal efficiency was achieved at aniline concentration of 100 mg L −1 with an applied voltage of 3.0 kV and pH 8.43. The removal efficiency decreased with the presence of radical scavengers, indicating that hydroxyl radical plays a key role in the degradation process. The removal efficiency increased obviously when Fe 2+ was added. Additionally, the intermediate products generated in the degradation process of aniline were analyzed by some analytical techniques, including total organic carbon analysis, ultraviolet-visible spectroscopy, Fourier Transform Infrared spectroscopy, Gas Chromatography-Mass Spectrometer, etc. The results showed that the degradation of aniline was mainly due to the strong oxidizing capacity of hydroxyl radical produced by the DBD plasma system. Based on the intermediate products identified in the study, the possible degradation mechanism and pathways were proposed. Graphical abstract: Image 1 Highlights: Atmospheric-pressure DBD plasma can degrade aniline effectively. The effect of different parameters on aniline degradation was studied. The intermediates products formed during the DBD plasma treatment were detected. The degradation pathways of aniline were proposed.